Nonlinear moving-horizon state estimation for hardware implementation and a model predictive control application - Brunello, Rafael Koji Vatanabe (2021)
Dissertação (mestrado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2021.